Information richness and trust in V-commerce: implications for services marketing - Chesney, Thomas; Chuah, Swee Hoon; Dobele, A.; Hoffmann, Robert (Emerald, 2017)
Purpose: The potential for e-commerce is limited by a trust deficit when traders do not interact in a physical, bricks-and-mortar context. The theory of information richness posits that equivocal interactions, such as ones requiring trust, can be facilitated through communication media that transmit multiple cues interactively. We examine the potential of information-rich virtual worlds to reduce this trust deficit compared with more traditional web-based e-tailing environments.